Economic impact assessment of rinderpest control in Africa - Tambi, N.E.; Maina, O.W.; Mukhebi, A.W.; Randolph, Thomas F. (World Organisation for Animal Health, 1999)
The authors assess the economic imapct of the Pan-African Rinderpest Campaign (PARC). The PARC programme commenced in 1986 with the objective to control and ultimately eradicate rinderpest from Africa. From among the thirty-five countries that participated in PARC, ten countries were selected for the analysis, based on data availability. The three following key socio-economic issues were addressed: cost-effectiveness, returns to investment and the welfare gains of the intervention. The standard cost-benefit approach based on a computer spreadsheet model was used to assess the economic impact of rinderpest control. Benefits of the intervention consisted of increased revenue due to avoided production losses. Estimates of the value of production losses were obtained under both `with PARC' and `without PARC' scenarios and the incremental benefits were derived as the difference between the two scenarios. In addition, an economic surplus model was used to assess the distribution of welfare effects generated by the intervention. Analysis of funding for the national campaigns showed roughly equal commitment to the programme by national governments and the principal donor, the European Union. Examination of the implementation costs in the ten countries indicated that with the exception of one country, PARC was implemented in a cost-effective manner with average costs appearing within a relatively narrow range. The figures obtained in ECU (European currency units) were between ECU0.27 and ECU0.60 per head of cattle vaccinated. The estimated average return from the ten countries (ECU1.8 for each ECU invested in the campaign) demonstrates that based on the sample of countries, rinderpest control in Africa has been economically profitable. In each of ten countries, estimated benefits at least covered the value of the investment in PARC. The programme has provided a total net present value of ECU29 million for the ten countries, suggesting that the implementation of PARC has been a wise public investment decision. Analysis of the distribution of the welfare gains from PARC revealed that producers derived the greater share of the ECU58 million in net value of production losses avoided due to rinderpest control in the ten countries. Consumer gains accounted for approximately one-fifth of the total, due to lower prices from increased supplies.